Thursday

November 27, 2014

November 27, 2014

Posted by **Beatrice** on Thursday, May 10, 2012 at 11:22pm.

(sin^3(x)+cos^3(x))÷(1-2cos^2(x)) = (sec(x)-sin(x))÷(tan(x)-1)

- Pre-calc -
**Steve**, Friday, May 11, 2012 at 12:17amon the LS,

sin^3+cos^3 = (sin+cos)(sin^2 - sin*cos + cos^2) = (sin+cos)(1-sin*cos)

1-2cos^2 = sin^2-cos^2 = (sin+cos)(sin-cos)

divide, giving (1-sin*cos)/(sin-cos)

on the RS,

sec-sin = 1/cos - sin = (1-sin*cos)/cos

tan-1 = sin/cos - 1 = (sin-cos)/cos

divide, giving (1-sin*cos)/(sin-cos)

LS = RS

**Answer this Question**

**Related Questions**

Pre-Calc - How would you prove this identity? (sin^3(x)+cos^3(x))÷(1-2cos^2(x...

Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x...

Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...

trigonometry hlp me - 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y...

precalculus - For each of the following determine whether or not it is an ...

MATH - Hi, I really need help with these questions. I did some of them halfway, ...

Pre-Calculus - I don't understand,please be clear! Prove that each equation is ...

trignonmetry - 6. Prove that tan λ cos^2 λ + sin^2λ/sin λ = ...

Pre-Calculus - Prove that each equation is an identity. I tried to do the ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...